The Analysis of Relationship Between Critical Thinking Ability in Early Childhood and Thematic Learning Outcomes - Rissa Megavitri; Devin Mahendika; Rahman Pranovri Putra; Apit Fathurohman; Yulius Luturmas (Journal of Childhood Development, 2023)
This study aims to determine the relationship between critical thinking skills and student learning outcomes, as well as to find out how much the level of critical thinking skills has to do with the thematic learning outcomes that the researchers concatenated into learning outcomes for Indonesian language, social studies, and civics in fifth grade elementary school students. This study used the descriptive-correlational method. The tools used to collect data are Likert scales and documents. The sample used is a saturated sample, that is, the entire population is 83 fifth-grade elementary school students. The correlation technique used in this research is product moment correlation, with the t-count results being 3,446 for Indonesian language learning outcomes, 2,819 for social studies learning outcomes, and 8,971 for civics learning outcomes. The results of the correlation between critical thinking skills and Indonesian learning outcomes are 0.253, 0.303 for social studies learning outcomes, and 0.258 for civics learning outcomes. So, the descriptive results are that there is a significant positive relationship between critical thinking skills and learning outcomes in social sciences and civics, with the level of relationship being at a moderate level.